The role of the transport system in destination development - Prideaux, Bruce (Tourism management (1982), 2000)
Although the transport industry provides the link between tourism generating and destination regions the industry's role as an agent in destination development has been largely overlooked. If the ability of tourists to travel to preferred destinations is inhibited by inefficiencies in the transport system there is some likelihood that they will seek alternative destinations. This paper outlines a transport cost model that identifies the significance of transport as a factor in destination development as well as in the selection of destinations by intending tourists. The model demonstrates the dynamic relationship between categories of holiday expenditure and tourists’ point of origin. Increased distance generally leads to increased transport access costs and represents a significant factor in total holiday cost. The model is tested by analyzing the role of transport in the development of Cairns as a destination by examining the effect of distance, transport access costs and competing destinations.